Heratic Virtual Keyboard with phonetic symbols: An application for adapted phonetic transcriptionn - Herrero, Ricard; Paula, José J. (Revista de Investigación en Logopedia, 2025)
Undergraduate students in language, linguistics, and speech therapy programs typically perform phonetic transcriptions by handwriting due to limited accessibility of phonetic symbols in standard computing systems. However, for some students with motor disabilities, manual writing may be challenging, which requires the acquisition of such skill to be aligned with their capabilities. This paper presents a software application initially developed for a student in the Catalan Philology degree with cerebral palsy and severe speech and handwriting difficulties, alongside the preliminary steps undertaken prior to implementing this digital tool. This application, Heratic Virtual Keyboard with phonetic symbols (HVK; ©Universitat de València – Estudi General, 2024), is an on-screen keyboard that enables standard typing, as with any virtual keyboard, and facilitates phonetic transcription through mouse clicks, significantly streamlining the transcription process in a digital environment. The HVK includes not only the alphanumeric elements of a typical physical keyboard but also the phonetic symbols and diacritics required by language and linguistics students for transcribing speech samples in Catalan, Spanish, Basque, and Galician.
Keywords: Cerebral Palsy; Motor impairment; Phonetic transcription; Virtual Keyboard